Genetic determination of replication of rice hoja blanca virus within its planthopper vector, Sogatodes oryzicola - Zeigler, Robert S.; Morales, Francisco José (Scientific Societies, 1990)
The inheritance of the ability of Sogatodes oryzicola to support replication of the rice hoja blanca virus (RHBV) was studied by following the segregation of progeny of crosses between insects of known pedigree and known ability to support virus replication and transmission. Virus transmission to plants required at least 20?25 days postacquisition incubation of RHBV in the insect. Enzyme-linked immunosorbent assay (ELISA) was developed to detect RHBV in vectors incubating, but not yet transmitting, the virus. A postacquisition incubation period in the insect of 12 days was required before the virus could be detected by ELISA (ELISA+), indicating that the virus replicates within the vector. Potential vectors were insects that did not transmit RHBV after feeding acquisition, not yet completing the incubation period, and were differentiated from nonvectors as being capable of supporting RHBV replication (ELISA+). Nonvectors were distinguished from vectors and potential vectors by their inability to transmit the virus to healthy plants and by their negative ELISA (ELISA?) values following acquisition feeding and a 14-day incubation. Progenies of nonvector parents from lineages including at least one vector were allowed to acquire RHBV and then were assayed for postacquisition increase in virus titer. The progeny segregated in a manner consistent with a single recessive gene controlling planthopper ability to support virus replication (1:3, ELISA+:ELISA?). The ELISA+ progeny could transmit RHBV after a normal incubation period. ELISA+ ? ELISA+ crosses of progeny from these crosses yielded all ELISA+ progeny. Progeny of crosses of combinations of ELISA+ and ELISA? segregated 1:1 or 0:1 (ELISA+:ELISA?). There was no evidence for sex linkage or determination of the ability to support RHBV replication; however, a strong maternal influence on progeny transmission ability was detected. Active female vectors transmitted RHBV transovarially to their progeny, regardless of the male parent and progeny genotype, and these could transmit the virus to plants. In progeny receiving the virus maternally, virus titers, as determined by ELISA, were lower and more variable in insects with a ELISA? male parent than in insects with two ELISA+ parents. Individuals with an ELISA? male parent, and that had acquired the virus from the female parent, could lose the ability to transmit it to plants. It is concluded that the identified recessive gene controls the ability to support virus replication but not transmission ability per se. The implications of these findings are discussed in relation to the epidemiology of RHBV.